Intraocular lens implants and risk of endophthalmitis. Issue 11 (1st November 1998) - Bainbridge, J W B; Teimory, M; Tabandeh, H; Kirwan, J F; Dalton, R; Reid, F; Rostron, C K
Abstract : AIM: To investigate the possible association between the use of three piece foldable silicone polypropylene (SPP) intraocular lenses (IOLs) and an increased risk of postoperative endophthalmitis. METHODS: A retrospective analysis was conducted of all cases of postoperative endophthalmitis following phacoemulsification surgery in a single unit over a 3 year period. The incidence of postoperative endophthalmitis in eyes with SPP IOLs was compared with the incidence in eyes with single piece polymethylmethacrylate (PMMA) IOLs. RESULTS: 772 cataract extractions by phacoemulsification were performed. One (0.16%) of the 622 patients with PMMA IOLs developed endophthalmitis. Excluding one patient who had aplastic anaemia, five (3.33%) of 150 patients with SPP IOLs developed endophthalmitis. The relative risk for postoperative endophthalmitis associated with the use of the SPP IOL compared with the PMMA IOL was 20.1 (p=0.015). CONCLUSION: This study adds further evidence to the concept that SPP IOLs can be a significant risk factor in the development of postoperative endophthamitis.